TATA CARA PELAKSANAAN LAMARAN DALAM UPACARA PENGANTIN TRADISI JAWA DI SURAKARTA - Ning Hadiati (Gelar : Jurnal Seni Budaya, 2006)
This Research focussed at existing symbol meaning in Java nuptials. Procedures Custom Java in nuptials have many small ceremony network which must be conducted. One of the ceremony network that is lamaran. Ceremony Lamaran represent event which is very awaited by putri temanten candidate side. In Lamaran condition with seimbolis. Without meaning of is existence of lamaran event, all ceremony network will fail and even will make disappointed and feel small on the side of putri temanten family Peningsed in the nature of' Ubarampe: Marginally paningset ubarampe consist of 3 matte; that is paningset bakuning, paningset abon-abon and paningset pangiring. brought goods by man temanten candidate side family. brought goods among others in the form of a set dress woman, Pamesing cloth, properties estae, wedding ring and Abon - abon as lamaran medium complement Each nuptials network have meaning meaning to organizer family pengantin. Ceremony marriage network among others is kumbokarnan ceremony - Ceremony Jonggolan - Ceremony Install Tuwuhan - Ceremony Lamaran/srah-srahan - Ceremony Siraman, Ceremony Paes, Ceremony Midodareni, Ceremony Nebus Kembar Mayang, Ceremony Execution Marriage ( Oath in marriage of Moslems and Reception}. Among the tradition ceremony network